Laudatio on the Doctor Honoris Causa Academic Title Awarding to Very Rev. Fr. Arturo Sosa Abascal, Superior General of the Society of Jesus - DIÓSI, Dávid (Studia Universitatis Babeș-Bolyai Theologia Catholica Latina, 2023)
In hoc Regno nostro eruditionis instituendaeque in liberalibus disciplinis iuventutis, Collegium societatis Jesu, in Civitate Coloswar erigendum atque construendum statuerimus, […], cuius maxime decori atque utilitati consultum semper esse cupimus, […] ut et ornamento et commodo illi sit. “In an effort to advance the sciences and to propagate the liberal arts among our youth, we have decided to establish and to construct a Jesuit College in the city of Cluj, in the sincere hope that this college may prove to be an advantage and an ornament to the city,” writes Kristóf Báthory in his letter to the Magistrate of the city of Cluj, dated 5 May 1580. One year later, on 12 May 1581, István Báthory, King of Poland and Prince of Transylvania, signed the founding document of the Jesuit College and Academia Claudiopolitana, which states that students of the institution may study both towards a bachelor’s and a master’s degree and a doctorate, as it is legal and customary in the academies of Italia, Gallia, Hispania, and Germania.